Meat consumption in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohorts: Results from 24-hour dietary recalls - Linseisen, J; Kesse, E; Slimani, N; Bueno-de-Mesquita, H; Ocké, M; Skeie, G; Kumle, M; Iraeta, MD; Gómez, P; Janzon, L; Stattin, P; Welch, A; et al. (2002)
Objective: To evaluate meat intake patterns in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohorts. Design and setting: 24-Hour dietary recalls were assessed within the framework of a prospective cohort study in 27 centres across 10 European countries by means of standardised computer-assisted interviews. Subjects: In total, 22 924 women and 13 031 men aged 35-74 years. Results: Mean total meat intake was lowest in the 'health-conscious' cohort in the UK (15 and 21 g day-1 in women and men, respectively) and highest in the north of Spain, especially in San Sebastian (124 and 234 g day-1, respectively). In the southern Spanish centres and in Naples (Italy), meat consumption was distinctly lower than in the north of these countries. Central and northern European centres/countries showed rather similar meat consumption patterns, except for the British and French cohorts. Differences in the intake of meat sub-groups (e.g. red meat, processed meat) across EPIC were even higher than found for total meat intake. With a few exceptions, the Mediterranean EPIC centres revealed a higher proportion of beef/veal and poultry and less pork or processed meat than observed in central or northern European centres. The highest sausage consumption was observed for the German EPIC participants, followed by the Norwegians, Swedish, Danish and Dutch. Conclusions: The results demonstrate distinct differences in meat consumption patterns between EPIC centres across Europe. This is an important prerequisite for obtaining further insight into the relationship between meat intake and the development of chronic diseases.